RELATIONSHIP BETWEEN IMPLIED PRODUCTIVITY OF RETENTION AND THE STOCK PRICE IN THE INDONESIA STOCK EXCHANGE - Kuntara, Antonius Diksa (Jurnal Fakultas Ekonomi, 2012)
The study is investigating the effect of the announcement of dividend policy to companys share price in a capital market in Indonesia. Specifically, the study is examining the implied productivity of retention and the share price around the announcement of companys dividend policy. Through the research question